TRACE ELEMENTS IN ANORTHITE MEGACRYSTS FROM THE KURILE ISLAND ARC: A WINDOW TO ACROSS-ARC GEOCHEMICAL VARIATIONS IN MAGMA COMPOSITIONS - Bindeman I.N.; Bailey J.C. (My University, 1999)
Anorthite megacrysts from twelve volcanic centers of the Kurile Island Arc were analyzed by the ion microprobe for concentrations of: Li, Be, B, F, Mg, P, Cl, K, Ti, Fe, Co, Rb, Sr, Y, Zr, Nb, Cs, Ba, La, Ce, Pr, Nd, Sm, Eu, and Pb. These 1–2-cm megacrysts are mainly found as early phenocrysts in basalts, but are also present in andesites, rhyolites and hybrid rocks from almost every studied volcanic center, both subaerial and submarine. Electron and ion microprobe studies show that the cores of these megacrysts are homogeneous and unzoned, whereas rims often result from overgrowth of sodium-richer plagioclase in equilibrium with its host, silica-richer melt. The cores of these megacrysts can be used to see back through fractional crystallization and magma mixing and serve as a `window' into an earlier basaltic stage of magmatic evolution. Petrological observations and numerical crystallization modeling indicate that highly anorthitic plagioclase is the first or second (after olivine) liquidus phase in high-Al basalts regardless of varying K2O contents across the arc.